2015
DOI: 10.1063/1.4904314
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on the relaxation of an excited nitromethane molecule in an argon bath

Abstract: Classical molecular dynamics simulations were performed to study the relaxation of nitromethane in an Ar bath (of 1000 atoms) at 300 K and pressures 10, 50, 75, 100, 125, 150, 300, and 400 atm. The molecule was instantaneously excited by statistically distributing 50 kcal/mol among the internal degrees of freedom. At each pressure, 1000 trajectories were integrated for 1000 ps, except for 10 atm, for which the integration time was 5000 ps. The computed ensemble-averaged rotational energy decay is ∼100 times fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…The initial vibrational decay rate begins to show a non-linear dependence on densities higher than ∼0.002 Å -3 corresponding to ∼250 atm at 800 K. This deviation implies the breakdown of the isolated binary collision model. The density dependence can be reasonably well represented by a combinatorial collision model proposed Rivera-Rivera et al 7 that represents the effect of interfering collisions of multiple bath gas atoms with the molecule. Rotational relaxation rates remain proportional to density over the full range of pressures studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial vibrational decay rate begins to show a non-linear dependence on densities higher than ∼0.002 Å -3 corresponding to ∼250 atm at 800 K. This deviation implies the breakdown of the isolated binary collision model. The density dependence can be reasonably well represented by a combinatorial collision model proposed Rivera-Rivera et al 7 that represents the effect of interfering collisions of multiple bath gas atoms with the molecule. Rotational relaxation rates remain proportional to density over the full range of pressures studied.…”
Section: Discussionmentioning
confidence: 99%
“…This method is free of the IBC assumption and any number of atoms as dictated by pressure can be involved in an inelastic collision with the molecule. There are only a recent few examples [6,7] of this approach in dense gases because of the computational expense of following bath gas collisions that largely serve only to maintain the thermal state of the bath. Only one of these examples, Rivera-Rivera et al [7] (hereafter identified as RWST), explicitly considered IBC breakdown and concluded that for nitromethane in an Ar bath at 300K it occurs at ~100 atm, a pressure well within the operating range of engines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A simulation similar to this one for C 6 F 6 + N 2 was recently reported for nitromethane in an Ar bath. 28 This work reports additional details and new extensions of the previous bath model simulations of IET for C 6 F 6 + N 2 . In the previous study, the sensitivity of IET to the form of the C 6 F 6 + N 2 intermolecular potential was investigated for a high N 2 bath density, and in the current work this investigation is extended to a low bath density.…”
Section: Introductionmentioning
confidence: 97%
“…These studies revealed that the energy transfer rate depends on the initial energy, bath temperature, and type of third-body collider. Computationally, classical trajectory calculations have been used to simulate collisions of polyatomic molecules with bath gases, revealing some fundamental mechanisms and trends of collisional energy transfer (see, e.g., [15][16][17][18][19][20][21][22] and references therein). Recent studies have demonstrated that the pressure-dependent rate constants for some unimolecular reactions can be quantitatively reproduced through master equation modeling using the energy transfer parameters obtained from classical trajectory simulations [23][24][25].…”
Section: Introductionmentioning
confidence: 99%